The protection of the environment during armed conflicts : international shared responsibility - Danese, Paula Monteiro (2023)
This thesis examines the protection of the environment during armed conflicts. The study is divided into three interdependent parts in the four Chapters. The first part presents the development of public international law about the protection of the environment, the rules applicable in armed conflicts, and the protective guidelines of human rights in both contexts. The second part involves a concrete analysis of the standards and rules for protecting the environment in armed conflicts, taking into account the responsibility of States, the guidelines of the International Committee of the Red Cross, and the Principles on the Protection of the Environment in Armed Conflicts, prepared by the United Nations Commission on International Law, this instrument is the theoretical framework of this thesis. The third part is the analysis of the two study cases chosen for the characterization of the protection of the environment in correlation with armed conflict. Among the hypotheses discussed, there is the one that understands that there is already a legal framework that protects the environment, the one that understands the insufficiency of norms in Public International Law to protect the environment and hold States internationally responsible for such a violation and the one that believes that the above-mentioned Principles would be an important step towards the complete protection of the environment and guidance on the international responsibility of States in this context. Before presenting the conclusions, the last Chapter also takes the opportunity to the possible application to the cases of the Principles elaborated by the International Law Commission retroactively, only by way of debate and development of legal reasoning on the hypotheses discussed. In a conclusion, the effective relationship between the environment, armed conflicts, and human rights is presented, demonstrating that the combination of these three areas has an important legal standard to protect the environment in armed conflicts, however, a specific instrument is an important step for the development of international law in the reality that 21st Century presents, that is why it is debatable the feasibility and consequences of having the Principles on the Protection of the environment in armed conflicts approved and future implementation in practice.